الزمان والسرد في الخطاب الشعري العربي المعاصر: قصيدة "ساعة في الجزائر" لفدوى طوقان أنموذجا - زواري، خولة (جامعة عبد الحميد مهري - قسنطينة 2, 2022)
تهدف هذه الدراسة إلى الوقوف على الزمان ودوره في تسريد الشعر، وكيف يساهم الزمن في منح النص الشعري طابعا سرديا، فيتحول زمن الشعر إلى زمن سردي وتصبح بذلك القصيدة الشعرية قصيدة قصصية تحضر فيها كل التقنيات الزمنية التي يتم من خلالها نقل مختلف الأحداث. تتخذ الدراسة من قصيدة ساعة في الجزيرة لفدوى طوقان أنموذجا للكشف عن تمثيلات الزمن الذي يتساوق مع غيره من التقنيات السردية الأخرى مؤكدا على علاقته الجدلية مع الذات التي تقدم داخليتها بأسلوب قوامه التذكر والحوار وكيفية حضوره وإشكالية تحولاته، وتأثيراته في الذات. This study examines time and its role in poetry, and the way it contributes to giving a narrative point of view to poems. The poetry time then becomes a narrative one, and the poem recites a short story in which all technical timelines are present, which then tell the different happenings. The paper studies the poem "an Hour in an Island" by Fadoua Touqan, as a model in order to unravel the time manifestations which goes along with other narrative techniques, confirming its argumentative relation with self, that presents its interior in a style based on remembering and dialogue, how it is present, the problem of its transformations, and its effects on the self.
Keywords: الشعر العربي -- السرد الأدبي -- الأدب العربي